Electoral campaign of mayoral candidates of Leon, Iloilo in the 1992 election. - Cababasay, Ivy C. (2001.)
This is a descriptive study of the electoral campaign of the six mayoral candidates of Leon in the 1992 election. The 1992 Leon mayoral candidates were Romulo Cabana, Neri Cabsaba, Alejandro Caelian, Jaime Calosing, Rodolfo Camarista and Ismael Candolada. This study aims to present a profile of the 1992 mayoral candidates: to determine the campaign resources; To analyze the campaign organization and the campaign strategies of mayoral candidates during the electoral campaign: to analyze the voters' choice and perceptions of the 1992 Leon mayoral electoral campaign: and, to analyze the electoral campaign of the mayoral candidates in the 1992 election in Leon. To satisfy these objectives, the researcher interviewed the mayoral candidates, some of their family members, their campaign staff and/or their representatives. A questionnaire was also formulated and was administered to the respondents. The findings of the study reveal that almost all mayoral candidates came from prominent families. Most of them came from the upper-middle class families except for Cabana and Cabsaba who considered their family as belonging to the lower class. Except for Romulo Cabana, all mayoral candidates in the 1992 election in Leon were college graduates. Except for Calosing and Camarista all four mayoral candidates had ran for an elective office prior to the 1992 election. The campaign resources particularly the material resources of a candidate were the determining factor in the success of his electoral campaign. It was also found out that most of the mayoral candidates have no formal structural organization in their electoral campaign except for Cabana and Calosing. Campaign strategies common among the mayoral candidates were holding of caucus in the barangays, distribution of leaflets, stickers, sample ballots and posting of streamers and other campaign materials. Character assasination and mudslinging were also present in the campaign. Voters were more interested in the personal issues raised against the mayoral candidates than their proposed programs of government or public concerns. They (voters) voted for the mayoral candidate based on the latter's personality or personal attributes. Personalities are more remembered than social and political issues. Although there was vote-buying in the 1992 election, the mayoral candidates and the voters themeselves considered it peaceful and orderly due to the absence of violence.
Thesis (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo
Keywords: Election -- 1992 -- Leon, Iloilo